Complex Instruction Team Product (CITP) learning model: Improving student’s scientific attitudes and learning outcomes - Dominggus Rumahlatu; Kristin Sangur; Sintje Liline (JPBI (Jurnal Pendidikan Biologi Indonesia), 2019)
Complex Instruction Team Product (CITP) learning model is one of the creative-innovative learning models which is assumed to be able to empower scientific attitudes and learning outcomes of students. This study aimed to determine students’ scientific attitudes and cognitive learning outcomes by implementing CITP learning model. This research used one-group pretest-posttest design. The sample was 18 tenth graders of academic year 2017/2018 of State Senior High School 6 of Ambon, Maluku Province. The data was analyzed using N-Gain test which then continued with dependent samples t-test. This result indicated that the highest achievement of students’ scientific attitudes were honesty and creativity (54). Meanwhile, the N-Gain score of students' cognitive learning outcomes was 0.61. In addition, the results of paired samples t-test show that there was a significant difference (p<0.05) between the students’ cognitive learning outcomes before and after the application of CITP learning model. This means that the application of CITP learning model can improve students’ scientific attitudes and cognitive learning outcomes.